MUSLIM WOMEN IN THE CURRENT SCENARIO: A BRIEF STUDY - Anjum, Shabana (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In this age of information technology, which has turned our world into a global village, it is pertinent to question what impact this recent development has had on the rights of Muslim women across the world. Having travelled to nine Muslim countries, from Pakistan and Bangladesh to the Gulf countries, Egypt, Syria and Lebanon, my answer would be that it is slowly, but surely, leading to reassessment and change. However, attempts to accelerate the pace of this change, without fully understanding its complex nature and without taking into account the deep commitment of most Muslim women to their spiritual and cultural authenticity, may halt or even reverse this process, which could be very costly for women and Muslim societies in particular. So, these are the challenges and opportunities.